Chemokine and cytokine measurements using Luminex and Selected Reaction Monitoring (SRM): comparing technologies - Nkonyane, Tshepiso Ruth (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.